2020
DOI: 10.1161/hypertensionaha.119.13715
|View full text |Cite
|
Sign up to set email alerts
|

Circ- calm4 Serves as an miR-337-3p Sponge to Regulate Myo10 (Myosin 10) and Promote Pulmonary Artery Smooth Muscle Proliferation

Abstract: Pulmonary artery smooth muscle cell proliferation is the pathological basis of pulmonary vascular remodeling in hypoxic pulmonary hypertension. Recent studies suggest that circular RNA (circRNA) can regulate various biological processes, including cell proliferation. Therefore, it is possible that circRNA may have important roles in pulmonary artery smooth muscle cell proliferation in hypoxic pulmonary hypertension. In the present study, we aimed to identify functional circRNAs and clarify their roles and mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 47 publications
1
71
0
Order By: Relevance
“…CircRNAs, as a recent identified member of the non-coding RNA family, will be a promising diagnostic and therapeutic target in PH ( Gokool et al, 2020 ). A series of cirRNAs have been found to participate in the development of PH, but only a few of them are clearly understood in terms of their distinct pathophysiological mechanisms ( Zhang et al, 2020 ). In order to better understand the in-depth mechanisms behind the pathogenesis of PH, we designed this study with the aim of investigating the roles of hsa_circ_0002062 in the viability and migration of hypoxic PASMCs via hsa-miR-942-5P-mediated regulation of CDK6.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs, as a recent identified member of the non-coding RNA family, will be a promising diagnostic and therapeutic target in PH ( Gokool et al, 2020 ). A series of cirRNAs have been found to participate in the development of PH, but only a few of them are clearly understood in terms of their distinct pathophysiological mechanisms ( Zhang et al, 2020 ). In order to better understand the in-depth mechanisms behind the pathogenesis of PH, we designed this study with the aim of investigating the roles of hsa_circ_0002062 in the viability and migration of hypoxic PASMCs via hsa-miR-942-5P-mediated regulation of CDK6.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences showed that circRNA functioned as miRNA sponge to promote the activity of mRNA [19][20][21]. Recently, researchers have focused on circRNA-miRNA-mRNA, as a novel regulatory mechanism of competing endogenous RNA (ceRNA), aiming at understanding RNA interactions deeply [22].…”
Section: Introductionmentioning
confidence: 99%
“…The chopped tissues were digested for two hours in 2 mg/ml collagenase II (Sigma, c6885). PASMCs were cultured in culture medium containing 20% fetal bovine serum 63 and 1% penicillin and streptomycin in a 5% CO 2 humidified incubator at 37°C. Before each experiment, the cells were incubated in DMEM 5% serum for 24 h. Cells in hypoxic culture were incubated in a Tri-Gas Incubator (Heal Force, Shanghai, China) with a gas mixture containing 92% N2-5% CO 2 -3% O 2 for 24 h.…”
Section: Cell Isolation and Culturementioning
confidence: 99%